Rethinking andragogical assumptions in the global age: how preferences for andragogical learning vary across people and cultures. Issue 1 (2nd January 2022) - Roessger, Kevin M.; Roumell, Elizabeth A.; Weese, James
ABSTRACT: We investigated whether andragogical assumptions and their common critiques are reflected in global PIAAC data using its motivation-to-learn (MtL) and elaboration scales. A preliminary validation study with 300 adults revealed that andragogical assumptions cluster on these scales' two factors. Using hierarchical linear modelling of PIAAC data, we then investigated whether andragogical learning preferences varied across countries, and as a function of a learner's age, gender, education level, and occupation type. We then identified six country-level predictors from relevant theory to explain cross-country variation. Preferences varied across countries, decreased with age, and increased with educational level and occupational skill. Men had stronger preferences than women. A country's cultural value dimensions and its ability to meet its citizens' basic needs explained about half of the variation in preferences across countries. Preferences for andragogical learning were highest in Western countries, and among adults with similar demographics as Knowles. Implications for research and practice are discussed.